2021
DOI: 10.1038/s41467-021-26545-9
|View full text |Cite
|
Sign up to set email alerts
|

A Slam-dependent hemophore contributes to heme acquisition in the bacterial pathogen Acinetobacter baumannii

Abstract: Nutrient acquisition systems are often crucial for pathogen growth and survival during infection, and represent attractive therapeutic targets. Here, we study the protein machinery required for heme uptake in the opportunistic pathogen Acinetobacter baumannii. We show that the hemO locus, which includes a gene encoding the heme-degrading enzyme, is required for high-affinity heme acquisition from hemoglobin and serum albumin. The hemO locus includes a gene coding for a heme scavenger (HphA), which is secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 65 publications
(113 reference statements)
1
41
0
Order By: Relevance
“…Recent discoveries have revealed that members of the DUF560 family of OMPs are Type XI secretion systems (TXISS) that can move proteins across the outer membrane (Hooda et al, 2016(Hooda et al, , 2017Fantappie et al, 2017;da Silva et al, 2019;Bateman et al, 2021;Grossman et al, 2021). TXISS-dependent effectors include binding proteins for transferrin, lactoferrin, factor H, and heme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent discoveries have revealed that members of the DUF560 family of OMPs are Type XI secretion systems (TXISS) that can move proteins across the outer membrane (Hooda et al, 2016(Hooda et al, , 2017Fantappie et al, 2017;da Silva et al, 2019;Bateman et al, 2021;Grossman et al, 2021). TXISS-dependent effectors include binding proteins for transferrin, lactoferrin, factor H, and heme.…”
Section: Discussionmentioning
confidence: 99%
“…X. nematophila HrpB and Acinetobacter baumanii HsmA are TXISS OMPs that secrete the soluble (non-lipidated) hemophores HrpC and HrpA, respectively. Xenorhabdus nematophila NilB is a TXISS OMP that, along with the associated lipoprotein NilC, is necessary for mutualistic colonization of the nematode Steinernema carpocapsae (Cowles and Goodrich-Blair, 2008;Hooda et al, 2016Hooda et al, , 2017Fantappie et al, 2017;da Silva et al, 2019;Bateman et al, 2021;Grossman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some Gram-negative pathogens encode multiple haem-acquisition systems such as the Phu and Has systems in P. aeruginosa 44 , suggesting that multiple non-redundant haem uptake systems benefit bacterial virulence. In the nosocomial pathogen Acinetobacter baumannii , the haemophore HphA is recognized by the two-component system receptor HphR 45 . Moreover, recent findings demonstrate that haem uptake efficiency is dependent upon bacterial toxin production in Vibrio cholerae 46 , raising the possibility that virulence factors may have a role in enhancing bacterial haem uptake in vivo.…”
Section: Fe In Infection and Immunitymentioning
confidence: 99%
“…The roles of heme in heme proteins are diverse; for instance, heme acts as an electron carrier [ 1 , 2 ], an active site for enzymes such as oxidoreductases [ 3 , 4 ], an oxygen storage molecule [ 5 , 6 ], a ligand for proteins [ 7 , 8 ], and an iron storage molecule [ 9 ]. Hemophore proteins bind heme for its transport or storage [ 10 ]. Heme is classified into several types according to its peripheral groups ( Figure 1 ), and the most common heme types are heme b and c [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%